Antimicrobial, photodegradation and BioReRAM applications of multifaceted green zinc oxide nanoparticles synthesized using coffee leaves extract - de Oliveira Arnoldi Pellegrini, Vanessa; de Jesus Bernardo, Aparecido; Rossi, Bruno Roberto; Leite, Ramon Resende; Possatto, João Fernando; Dabul, Andrei Nicoli Gebieluca [UNESP]; Fontana, Carla Raquel [UNESP]; Dlamini, Zolile Wiseman; Mahule, Tebogo Sfiso; Mosepele, Belda Q.; Thema, Force Tefo; Mamba, Bhekie B.; et al. (Springer Nature, 2025)
The comprehensive utilization of plant biomass is a cornerstone in the development of sustainable circular bioeconomy. Several studies explore the conversion of primary biomass polymers and macromolecules, such as cellulose, hemicellulose, and lignin, into value-added chemical compounds, sustainable materials and biofuels. However, extractives warrant further investigations. Coffee, being one of the most consumed and produced global commodity and therefore widely available in a number of countries, presents an exciting study case. Here, we have employed fresh coffee leaves extract for the synthesis of zinc oxide nanoparticles (ZnO NPs). The synthesized ZnO NPs were characterized, including ultraviolet-visible and Fourier transform infrared spectroscopies, dynamic light scattering, scanning electron microscopy, X-ray diffraction, electron paramagnetic resonance, energy-dispersive X-ray spectroscopy, and thermal gravimetric analysis. Nanoscale size and reduced optical bandgap (3.2 eV) of the ZnO NPs contributed to their significant antimicrobial and photodegradation effects. Furthermore, with the aim of producing biological Resistive Random-Access Memory (bioReRAM) devices, we successfully explored the resistive switching properties of chitosan polysaccharide doped with the ZnO NPs.